The Future of Immunotherapy: A 20-Year Perspective - Wraith, David C. (Frontiers in Immunology, 2017)
Immunotherapy is the field of immunology that aims to identify treatments for diseases through induction, enhancement or suppression of an immune response. Immunotherapies designed to instigate or enhance an immune response are considered ‘activating immunotherapies’ while those designed to repress an immune response are ‘suppressive immunotherapies’. This perspective will focus on two areas of immunotherapy, activating immunotherapies for cancer and suppressive immunotherapies for autoimmunity both of which have seen a resurgence in interest in recent years and are likely to transform the treatment of many human diseases in the next 20 years.